2021
DOI: 10.1088/1361-6463/ac4135
|View full text |Cite
|
Sign up to set email alerts
|

Charge carrier dynamics and photovoltaic properties of near-infrared absorbing squaraine incorporated solution-processed additive-free PTB7:PCBM based ternary solar cells

Abstract: The introduction of a third component vehemently modifies the morphology and charge carrier dynamics in the blend of a donor-acceptor pair, thereby affecting the photovoltaic properties of organic solar cells (OSCs). Combining steady-state, impedance, and transient spectroscopic measurements, photovoltaic properties of 2,4-bis[4-(N,N-diisobutylamino)-2,6-dihydroxyphenyl] squaraine (DIB SQ) incorporated additive-free PTB7:PC70BM OSCs are assessed. As observed from steady-state measurements, concomitant enhancem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 44 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…Though the increment in thickness of the active layer can reduce the value of J d significantly, a trade-off exists between J ph and J d , when the active layer thickness is increased beyond a certain limit. The high P c values under short-circuit condition for all three devices indicate efficient exciton dissociation and charge collection without the assistance of external reverse bias. ,, It further suggests that the photodiodes can be utilized for panchromatic photodetection in a self-powered mode.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…Though the increment in thickness of the active layer can reduce the value of J d significantly, a trade-off exists between J ph and J d , when the active layer thickness is increased beyond a certain limit. The high P c values under short-circuit condition for all three devices indicate efficient exciton dissociation and charge collection without the assistance of external reverse bias. ,, It further suggests that the photodiodes can be utilized for panchromatic photodetection in a self-powered mode.…”
Section: Resultsmentioning
confidence: 79%
“…The high P c values under short-circuit condition for all three devices indicate efficient exciton dissociation and charge collection without the assistance of external reverse bias. 18,26,27 It further suggests that the photodiodes can be utilized for panchromatic photodetection in a self-powered mode.…”
Section: Resultsmentioning
confidence: 99%
“…After adding PDTSTPD, the PCE was enhanced to 20.8%, supporting the success of the ternary strategy for indoor OPV devices. The authors found that the values of FFs were the primarily improved factor in the ternary devices; hole mobility was increased and shallow traps near the band edges were passivated through blending the PDTSTPD as the ternary component [66,76].…”
Section: The Ternary Strategymentioning
confidence: 99%